Recent Submarine Landslides on the Continental Slope of Storfjorden and Kveithola Trough-Mouth Fans (North West Barents Sea) - Lucchi, Renata G.; Pedrosa-González, María Teresa; Camerlenghi, Angelo; Urgeles, Roger; De Mol, Ben; Rebesco, Michele (Kluwer Academic Publishers, 2012)
Submarine Mass Movements and Their Consequences, 5th International Symposium.-- 11 pages, 5 figures Up to 12 submarine landslides retain a morphological evidence as concave amphitheater-like depressions of various sizes on the middle and upper slope of the Storfjorden and Kveithola Trough-Mouth Fans (TMFs), NW Barents Sea. The largest of them show lateral scarps 35–40 m high that reach the continental shelf edge and cover an area of at least 1,120 km2. Submarine landslides are translational, with headwall and laterals scarps clearly cut into Last Glacial Maximum debris flows deposits. The largest landslides seem to be rooted at the base of a terrigenous/hemipelagic sedimentary unit inferred to be of Middle Weichselian age (Marine Isotopic Stage 3). Stratigraphic, lithological and geotechnical observations suggest that the rapid deposition of a thick sequence of fine-grained, high water content interlaminate plumites is the most important controlling factors in the generation of submarine landslides on the southern Storfjorden and Kveithola TMFs This study is supported by Spanish IPY projects SVAIS (POL2006-07390/CGL) and IPY-NICE STREAMS (CTM2009-06370-E/ANT), the Spanish project DEGLABAR (CTM2010-17386) and by OGS IPY Project EGLACOM Peer Reviewed